(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Ursula K. Le Guin is frequently celebrated for her radical reimagining of gender, culture, and society within speculative fiction; however, critical discussions often underplay the significance of her ethnic positionality as a white American writer in shaping these imaginative worlds. This article argues that Le Guin’s early exposure to anthropology and Indigenous cultural frameworks mediated through her upbringing in an intellectually cross-cultural environment produced a hybrid epistemic identity that profoundly influenced her literary world-making. Rather than writing from an unexamined position of Western authority, Le Guin transforms her whiteness into a site of ethical questioning and cultural reflexivity. Through a close reading of The Left Hand of Darkness (1969) and Always Coming Home (1985), this study demonstrates how Le Guin’s speculative societies resist fixed notions of gender, ethnicity, linear progress, and imperial dominance. The androgynous world of Gethen and the future ethnography of the Kesh people reveal a sustained critique of Western binaries and colonial modes of knowledge production. By situating Le Guin’s fiction within debates on ethnicity, anthropology, and cultural hybridity, this article offers a nuanced understanding of how early cultural exposure shaped her lifelong engagement with alternative futures. The study contributes to scholarship on speculative fiction by foregrounding authorial ethnicity as a productive, rather than limiting, force in literary imagination.